2021
DOI: 10.3390/jcm10112444
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals of Thyroid Function Tests Assessed by Immunoassay and Mass Spectrometry in Healthy Pregnant Women Living in Catalonia

Abstract: Background: Recent guidelines recommend establishing a local reference interval (RI) for thyroid function. We aimed to establish trimester-specific RIs for thyrotropin (TSH) and free thyroxine (FT4) in a cohort of healthy pregnant women in Catalonia (Spain). Methods: A prospective observational study was conducted with 332 healthy pregnant women, from the first trimester (1T) to delivery. TSH was measured using an Architect® immunoassay (Abbott) and FT4 by two immunoassays, Architect® (Abbott) and Cobas® (Roch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Until then, assay specific reference intervals for pregnant women, ideally per trimester, are necessary. Reference intervals in pregnant women for different trimesters were established for several immunoassays of Roche, Abbott, Beckman Coulter and Siemens and an ultrafiltration LC-MS/MS method as well [41][42][43][44][45][46][47][48][49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…Until then, assay specific reference intervals for pregnant women, ideally per trimester, are necessary. Reference intervals in pregnant women for different trimesters were established for several immunoassays of Roche, Abbott, Beckman Coulter and Siemens and an ultrafiltration LC-MS/MS method as well [41][42][43][44][45][46][47][48][49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…44 Another study used liquid chromatography-tandem mass spectrometry and immunoassay techniques; FT4 showed significant differences between these techniques during the first trimester, while no significant difference was noticed regarding TSH. 45 A study from China showed a considerable decline in TSH values during the first trimester compared to non-pregnancy values, while there was an increase in the second trimester, and throughout pregnancy, there was a gradual decrease in FT4 and FT3. 46 Another study done by Kurioka, et al, in Japan indicated significant changes in TSH and FT4 during the first trimester and showed a substantial decrease of FT4 during the progress of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…D concentrations depending on the assessment of 25(OH)-D regarding the commercial kits’ instructions (Immunodiagnostic-AG, Bensheim, Germany) [ 22 ]. Chemiluminescence immunoassay assay (CLIA) was used for measuring the serum concentrations of free thyroid hormones: T4 and TSH, using commercial kits (Architect ® CLIA, Abbott Diagnostic, Longford, Ireland) [ 23 , 24 ]. The enzymatic colorimetric method was used for the estimation of creatinine (Cr) by Siemens ADVIA Enzymatic reagent according to kits’ instructions (National Institute for Standards and Technology) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%